RELIGIOUS HARMONY THROUGH THE AGUSTUSAN THANKSGIVING TRADITION: A CASE STUDY OF SEGARAN VILLAGE, WATES DISTRICT, KEDIRI REGENCY - Aprilia Lestari; Melinda Nur Fara; Nur Aini Rahmaningrum; M Thoriqul Huda (2025)
Indonesia, a country rich in diverse religions, ethnicities, and cultures, has always prioritised interfaith harmony as one of the key aspects necessary to maintain national unity and cohesion. Harmony is defined as a state of calmness, harmony, and mutual respect. In this context, local wisdom plays a crucial role in preserving diversity, serving as a guiding principle that encourages mutual respect, appreciation, and the cultivation of tolerance within a diverse society. Local traditions, known as